(untitled) (Bangladesh Journal of Neuroscience, 2016)
Stroke is one of the foremost causes of morbidity, mortality and is a socioeconomic challenge. This is particularly true for developing countries like Bangladesh, where health support system including the rehabilitation system is not within the reach of common people. Hypertriglycerademia has an effective influence in the pathogenesis of Ischaemic Stroke (IS). So, the focus of this study was to evaluate and assess the association of serum triglyceride level in patients of IS. This case control study was carried out in the Department of Neurology in collaboration with Department of Biochemistry, BSMMU, Dhaka from July 2011 to June 2013. In this study, 60 diagnosed cases of ischaemic stroke patients and 60 age and sex matched healthy controls were enrolled. Risk factors of Ischemic Stroke (IS) patients were assessed ( adjusted Odds Ratio) in comparison with healthy adults. In this study, being married [OR. 1.95, 95% CI (0.40-9.42), p=0.409] , smoker [OR.1.65, 95% CI (0.57 - 4.82),p= 0.357], DM [OR. 1.48, 95% CI (0.36-6.06), p=0.582 ], IHD [OR. 1.51, 95% CI (0.29 – 7.89), p=0.624] , HTN [OR. 3.66, 95% CI (1.11–12.12), p=0.033] , overweight [OR.2.31, 95% CI (0.77 – 6.91), 0.135] and obesity [OR. 16.19, 95% CI (1.31–200.6), p=0.030] , increased level of serum TC [OR.8.24, 95% CI (2.07 – 32.83), p=0.003], TG [OR. 9.40, 95% CI (1.17 -75.86), p=0.035], LDL [OR. 0.45, 95% CI (0.10–2.05), p=0.308],and decreased level of HDL [OR. 3.37, 95% CI (1.03 - 12.25), p=0.045] were found as risk factors in developing IS. Independent t-test was done to find out the statistically significant differences of continuous variables like serum lipid profile between case and control group. The mean (SD) value of TG which is focus of this study, was found 237.67 (61.74) in case group, and 169.97 (26.95) in control group which was highly statistically significant (p < 0.0001). All of the significant variables were entered into stepwise logistic regression analysis model. From the logistic regression model, it can be finally concluded that hypertension, obesity, increased level of TC, increased level of TG and decreased level of HDL were statistically significant risk factors for development of IS. Bangladesh Journal of Neuroscience 2016; Vol. 32 (1): 34-38